The Art of Fiction No. 234. - Gebremedhin, Thomas (Paris Review)
An interview with the American novelist, Walter Mosley is presented. He speaks about his childhood interests, memory of Watts riots in Los Angeles, California and his foray into writing after moving to New York. When asked when did he leave California Mosley replies he left when he wanted to go as far away from his parents as he could. He also speaks about his literary work and social impact on his writings.